Measurement of the ZZ production cross section and limits on anomalous neutral triple gauge couplings with ATLAS - Mengarelli, Alberto <1981> (Alma Mater Studiorum - Università di Bologna, 2013)

(untitled)
The main work of this thesis concerns the measurement of the production cross section using LHC 2011 data collected at a center-of-mass energy equal to 7 TeV by the ATLAS detector and resulting in a total integrated luminosity of 4.6 inverse fb. The ZZ total cross section is finally compared with the NLO prediction calculated with modern Monte Carlo generators. In addition, the three differential distributions (∆φ(l,l), ZpT and M4l) are shown unfolded back to the underlying distributions using a Bayesian iterative algorithm. Finally, the transverse momentum of the leading Z is used to provide limits on anoumalus triple gauge couplings forbidden in the Standard Model.